The impact of Employee Motivation on Organisational productivity: A Case Study of Century Bottling Company - Wilson Katwesime (Uganda Christian University, 2023)
The study investigated impact of employee motivation on organizational productivity at century bottling company Namanve, Kampala. The objectives of the study were; I) To assess the various forms of staff motivation, ii) To find out staff motivation challenges impending on organization productivity, iii) To suggest the solution to the staff motivation challenges The study used cross-sectional research design in nature and this helped in collecting data from a wide section of study respondents. A sample of 30 employees century bottling company was used. Data was analyzed using frequencies and percentages were derived for easy interpretation and statistical tools like tables and figures were used. The findings indicated that employee motivation is a leading factor in organizational productivity that is to say, motivation affects performance positively at century bottling company in that. it increases productivity it enhances job satisfaction and increase knowledge and skills when performing the work. It finally recommended that employers should always give the tests to employees that have attained staff motivation and welfare during evaluation to see if it was conducted effectively. In conclusion, the management of century bottling company should ensure that they do all the activities that are under the motivation programs in order to achieve effective leading to employee performance in the company.